PERAN RUANG PUBLIK PERKOTAAN DALAM MENDORONG BUDAYA POLITIK INKLUSIF DI KOTA MAKASSAR - Sriany Ersina (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2025)
Urban public spaces serve as vital social platforms where interactions between diverse groups occur, potentially strengthening an inclusive political culture. This study seeks to find out how the design, management, and utilization of public spaces in Makassar City promotes civic political involvement. The methodology used is qualitative, using a case study approach that includes comprehensive interviews, participatory observations, and documentation analysis. The data was studied using NVivo software to uncover prominent themes arising from socio-political engagement in public locations such as Losari Beach, Karebosi, and Fort Rotterdam. The findings suggest that carefully designed public spaces can act as catalysts for fostering a participatory political culture, despite structural barriers such as inadequate supportive regulations and limited access. The results of this study provide a basis for formulating recommendations aimed at improving democratic and socially fair public space planning. Keyword: Public Space, Urban, Political Culture, Makassar City